Benchmarking Immunization Program Performance in the Africa Region - World Bank (Washington, DC, 2012)
The report intends to help shape the Africa Region's engagement in immunization, and, its major findings both validate conventional wisdom on immunization, and challenge the development community to explore new interventions. According to the study, the majority of countries in Sub-Saharan Africa have well-performing, or improved immunization programs reflecting the high priority governments and development partners attach to this basic health service. The overriding message is that robust implementation was essential to sustained success in the countries profiled in the case studies, and, countries found their own solutions, and pursued different strategies. The report also raises some provocative questions about the relationship between different programmatic instruments, and immunization program performance. Finally, some of the case studies highlight how programs are adapting to the rapidly changing environment in which development interventions are taking place. This new application of the benchmarking methodology may be of interest to immunization program managers, whose process can be used to analyze performance variation among districts, and to develop action plans for addressing major bottlenecks in the periphery. The report further emphasizes the importance of remaining vigilant, as performance can rapidly deteriorate with mounting fiscal pressures, and competing public health priorities. Ultimately, enhancing and sustaining immunization program performance will help ensure a healthy start to life for each new generation of children.